The Effectiveness of Professional Development Programs for School Administrators in Sultanae of Oman - Alhajri, H.; Rahman, A. (2011)
The purpose of this study was to investigate the effectiveness of professional development programs for school administrators to improve them in basic and post basic education. Many PDP have been done by the Muscat Governorate of Education and a lot of money has been spent in implementing the programs over the last thirteen years for development, enrichment and remedial (knowledge, skills and attitudes of school administrators). Two types of data were collected and used in this study; qualitative and quantitative data to provide valid and more reliable research findings. Qualitative data were gathered from interviews and document analysis and quantitative data were retrieved from a set of questionnaires. The data were analyzed using descriptive statistics. The research investigated the effectiveness of the PDP as perceived by the programs participants. The population for this research was 250 school administrators (principals and assistants), in Muscat Governorate of Education. Two hundred and fifteen questionnaires were returned and completed by respondents (77 male and 138 female). Respondents completed a research survey designed to measure perceptions of 77 items for six domains including availability and practice level, level of effectiveness of the programs and the difficulties that hinder effectiveness of PDP. The conceptual framework was based on CIPP Model as proposed by Stufflebeam (2003). The findings of this research indicated that the majority of respondents felt that professional development programs were important and not a waste of time. At the same time they requested organizers to be more concerned when implementing PDP. Although document analysis indicated that there were two kinds of PDP (training & qualification) most programs tended in the same direction. Another significant finding indicates the limited opportunities for PDP; programs not on the right track; lack of scholarships, the work leave system to continue higher education, opportunities for attending conferences inside and outside the country, for exchange visits outside the region and opportunity to participate in training courses outside the Sultanate of Oman were considered crucial among administrators. Another finding in the availability level indicates that there were significant differences in favor of female participants. The findings show that the respondents felt that the planning of PDP could be improved in many aspects such as training needs procedure, weakness of participation administrators when planning of PDP and there were no long term plans for PDP, although planning of PDP was considered the first step to get high level advantages. Other challenges in PDP were: how to correlate between the theoretical side and the practical side in development programs, the limitedness of exchange visits; assessing student learning or the specification of the programs and the targeted staff in the PDP; meetings do not provide solutions to educational issues; lack of cooperation between departments in conveying knowledge to school principals; trainers are in efficient due to the lack of cooperation with the different educational institutions and the method of preparing the work papers is not realistic.